Hakekat Supervisi dalam Pendidikan Agama Islam - Burhanuddin, Burhanuddin; Husnia, Husnia; Fatimah, Mety (Lembaga Yasin AlSys, 2026)
Supervision is a key component in improving the quality of education, including Islamic Religious Education (PAI), as it functions not only as administrative oversight but also as a professional development effort for teachers to ensure that the learning process is effective, systematic, and aligned with the aims of Islamic education. This article aims to examine the nature of supervision in Islamic Religious Education in terms of its concepts, objectives, principles, and its role in enhancing the quality of PAI learning. The method employed is library research, involving analysis of various relevant books and scholarly journal articles. The review findings indicate that supervision in Islamic Religious Education has distinctive pedagogical, spiritual, and moral dimensions, and therefore its implementation must be grounded in Islamic values such as sincerity, amanah (trustworthiness), and responsibility. The study concludes that supervision which is effective and oriented toward the professional development of teachers contributes to the continuous improvement of PAI learning quality and can serve as a foundation for developing educational supervision policies and practices that are more humanistic and endowed with transcendental value. Keywords: Educational Supervision; Islamic Religious Education (PAI); Teachers’ Professional Development; Quality of PAI Instruction; Library Research